Peran Teknologi Informasi dan Komunikasi dalam Wisata Halal di Sabang - Amru Yasir; Budiman Purba (Jurnal Pengabdian Masyarakat, 2025)
The development of halal tourism in Sabang, Aceh, is a crucial strategy for increasing the appeal of Islamic-based tourism in Indonesia. Sabang boasts significant potential, thanks to its natural beauty, strong Islamic culture, and the implementation of sharia law, which supports the comfort of Muslim tourists. In the digital era, information and communication technology (ICT) plays a key role in expanding promotional reach, improving service quality, and strengthening the image of halal destinations. Through the use of social media, halal tourism apps, online reservation systems, and digital platforms for MSMEs, halal tourism in Sabang can be effectively promoted to both domestic and international tourists. This article aims to analyze the role of ICT in supporting halal tourism development in Sabang, using a community service approach through field observations, interviews, and digital training. The study results indicate that the integration of digital communication and information technology can increase local community participation, expand market access, and strengthen the halal tourism ecosystem. Thus, ICT serves not only as a promotional tool but also as an instrument for community empowerment and strengthening the local economy.